Making Variety of Processed Gonggong Snails Become Culinary Alternatives in Bintan Island for The Community of Tanjung Talok, Teluk Sasah Village - Hary Jocom; Yudy Sunantri; Desi Herlina; Marchelino Aditya Prayoga; Lilis Sri Handayani; Mecaria Desifirsta Sibuea; Sinta Monalisa Situmorang (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Gonggong is known as a typical food from the island of Bintan, but its processing is only limited to boiling. Departing from this phenomenon, the main purpose of implementing community service is to diversify processed barking which economically has added value, and can be done on a household scale. Based on these main considerations, the objectives of PkM are: (1) Equipping the public with basic knowledge of entrepreneurship and product marketing; (2) Train the community to make various processed barks into barking prata and barking brains; and (3) Manufacture of processed drinks. The method used is through training which includes lectures, discussions, and most of the demonstration activities or practice of processing barking and drinks by involving participants in a participatory manner. This activity was attended by 23 participants consisting of women's groups in Tanjung Talok. Participants' assessment of organoleptic showed good numbers, even in terms of taste 93% said they really liked it, as well as other assessment components. However, the implications of this activity have not had a broad impact on building the entrepreneurial spirit of the community, only 13% (3 people) consistently start a household-scale entrepreneur, due to many factors that contribute to this condition.